1995
DOI: 10.3146/i0095-3679-22-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Breeding Sclerotinia Blight-Resistant Runner-Type Peanut1

Abstract: Field screening tests were conducted in 1991, 1992, and 1993 to identify Sclerotinia blight-resistant runner-type peanuts. Selections were made from three populations, “backcross to runner,” “backcross to Tamspan 90,” and “single cross.” Runner parents were chosen for agronomic qualities and resistance to other pathogens. Resistant (Spanish) parents used were cultivar Tamspan 90 and TxAG-5 germplasm. Families within populations were planted as single row 3 × 0.9-m plots. Repeated plant-by-plant inspections (PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Both Tamspan 90 and Southwest Runner are consistently among the most resistant cultivars in field evaluations. Ratings from assays designed to identify physiologic resistance on whole or detached plant parts are generally not well correlated with field screenings (1,15,20,21) Tamspan 90 was grown on nearly all of the problem fields in Oklahoma during the 1990's, but susceptibility to web blotch (caused by Phoma arachidicola Marassas, G.D. Pauer & Boerema) and reduced demand for spanish peanut have contributed to the increase in acreage planted to runner cultivars. While Southwest Runner is partially resistant to Sclerotinia blight, it was never accepted by the shelling industry because of its small seed size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both Tamspan 90 and Southwest Runner are consistently among the most resistant cultivars in field evaluations. Ratings from assays designed to identify physiologic resistance on whole or detached plant parts are generally not well correlated with field screenings (1,15,20,21) Tamspan 90 was grown on nearly all of the problem fields in Oklahoma during the 1990's, but susceptibility to web blotch (caused by Phoma arachidicola Marassas, G.D. Pauer & Boerema) and reduced demand for spanish peanut have contributed to the increase in acreage planted to runner cultivars. While Southwest Runner is partially resistant to Sclerotinia blight, it was never accepted by the shelling industry because of its small seed size.…”
mentioning
confidence: 99%
“…Partial resistance in these market types has two forms. Physiologic resistance is expressed as reduced lesion expansion over time as measured on inoculated seedlings or detached plant parts following incubation under artificial conditions favorable for disease development (1,4,15,20,21). Architectural or morphological resistance is expressed in some genotypes with an erect growth habit and sparse plant canopy that results in reduced contact of main and lateral stems with mycelium from the germinating sclerotia or adjacent infections; and/or reduced periods of microclimate favorable for disease development compared to spreading genotypes with a dense canopy (1,4,6).…”
mentioning
confidence: 99%
“…The assay was particularly useful in identifying susceptible entries: plants that were susceptible in the assay had an 87% chance of being susceptible in the field. However, plants identified as being resistant in the laboratory assay had only a 33% chance of being resistant in the field (Goldman et al, 1995). In Australia, Cruickshank et al (2002) also reported a significant correlation between one year of field results and an assay similar to the one used by Goldman et al In contrast, Hollowell et al (2008) did not find that intact plant assays correlated well with four years of field data, but the correlation improved significantly when field data from a year with low disease pressure was removed from the analysis.…”
mentioning
confidence: 99%
“…Some assays used main stems and lateral branches of whole, intact plants (Goldman et al, 1995;Cruickshank et al, 2002;Woodward et al, 2006;Hollowell et al, 2008). Goldman et al (1995) inoculated non-detached main stems of six-week-old plants with S. minor and found a significant relationship using a chisquare test between three years of field results and the laboratory assays. The assay was particularly useful in identifying susceptible entries: plants that were susceptible in the assay had an 87% chance of being susceptible in the field.…”
mentioning
confidence: 99%
“…The assay was particularly 54 useful in identifying susceptible entries: plants that were susceptible in the assay had an 87% 55 chance of being susceptible in the field. However, plants identified as being resistant in the 56 laboratory assay had only a 33% chance of being resistant in the field (Goldman et al, 1995). 57…”
mentioning
confidence: 99%